TYPES OF PROPERTY IN THE ARMED FORCES OF UKRAINE - Новікова, Є. (Київський національний університет імені Тараса Шевченка, 2022)
The article analyzes types of property in the Armed Forces of Ukraine and considers several options for its division. Contradictions between the Laws of Ukraine "On the Legal Regime of Property in the Armed Forces of Ukraine" and "On Economic Activity in the Armed Forces of Ukraine" were established, that make it possible to assume the presence of property other than military in the Armed Forces of Ukraine, and ways to eliminate it were proposed. Taking into an account the possibility of military units to carry out economic activity, property in the economic sector was separated from military property and classified in accordance with Art. 139 of the Commercial Code of Ukraine. The definitions of "economic activity" reflected in the Commercial Code of Ukraine, the Law of Ukraine "On Economic Activity in the Armed Forces of Ukraine" and the Regulation on the military (ship) economy of the Armed Forces of Ukraine, approved by the Order of the Ministry of Defense of Ukraine dated 16.07.1997 № 300, are compared. It is justified that the economic activity of the Armed Forces of Ukraine must be understood in the sense given by the Commercial Code of Ukraine and the Law of Ukraine "On Economic Activity in the Armed Forces of Ukraine". At the same time, the Regulation should be altered: firstly, by excluding of the alternative definition of the organization and management of military (ship) economy – the phrase "economic activity"; secondly, by defining an organization and management of the military (ship) economy as an activity of authorized entities, the main tasks of which are comprehensive and permanent providing of combat training and mobilization readiness of military units and formations, creation of conditions for their rapid transition from peaceful state to martial law. It was established that the definitions of military property and military (ship) economy are identical, and therefore the division of military (ship) economy is applicable to military property. The classification of property in the Armed Forces of Ukraine according to the sources of its acquisition is proposed.

Проаналізовано види майна в ЗС України та розглянуто декілька варіантів його поділу. Встановлено суперечність приписів Законів України "Про правовий режим майна у Збройних Силах України" та "Про господарську діяльність у Збройних Силах України", що дають змогу припускати наявність у ЗСУ іншого, ніж військове, майна та запропоновано шляхи її усунення. Зважаючи на можливість військових частин здійснювати господарську діяльність, у складі військового майна виокремлено майно у сфері господарювання та проведено його класифікацію відповідно до ст. 139 ГК України. Зіставлено зміст поняття "господарська діяльність", відображеного в ГК України, Законі України "Про господарську діяльність у Збройних Силах України" та Положенні про військове (корабельне) господарство ЗСУ, затвердженому Наказом Міністерства оборони України від 16.07.1997 № 300. Обґрунтовано, що господарську діяльність ЗС України необхідно розуміти в значенні, наведеному в ГК України та Законі України "Про господарську діяльність у Збройних Силах України". Водночас, у Положення мають бути внесені зміни шляхом: по-перше, виключення альтернативної назви організації та ведення військового (корабельного) господарства – словосполучення "господарська діяльність"; по-друге, визначивши організацію та ведення військового (корабельного) господарства як діяльність уповноважених суб'єктів, основними завданнями якої є всебічне і безперервне забезпечення бойової підготовки та мобілізаційної готовності військових частин і з'єднань, створення умов для швидкого переходу їх із мирного на воєнний стан. Констатовано тотожність визначень військового майна та військового (корабельного) господарства, а отже, встановлено застосовність поділу майна військового (корабельного) господарства до військового майна. Запропоновано класифікацію майна в ЗСУ за джерелами його набуття.
ВИДИ МАЙНА У ЗБРОЙНИХ СИЛАХ УКРАЇНИ
Keywords: military property; property in the Armed Forces of Ukraine; military (ship) economy; economic activity; legal regime of property; військове майно; майно в ЗСУ; військове (корабельне) господарство; господарська діяльність; правовий режим майна